Patient Attitudes Toward Exercise During Pregnancy [34R]. (May 2017) - Lott, Melisa; Schulkin, Jay; Power, Michael; Mackeen, A. Dhanya
Abstract : INTRODUCTION: Maintaining a healthy lifestyle during pregnancy includes engaging in 30 minutes of moderate activity most days of the week. We sought to determine the attitudes of pregnant patients towards exercise and their access to counseling regarding safe exercise options. METHODS: From December 2015 to May 2016, women receiving prenatal care completed an anonymous survey that included questions about their exercise habits and their exposure to counseling regarding physical activity recommendations. RESULTS: One hundred eighty women completed the survey: 96.1% were Caucasian and 45.0% were obese. Most women (80.3%) planned to do low-impact cardiovascular exercise during pregnancy. The average number of days/week that patients exercised regularly during pregnancy were quantified: zero days (21.2%); 1-2 (47.5%); 3-4 (20.1%); 4-5 (6.1%) and 5+ (5.0%). Nineteen percent of patients reported they were not counseled regarding exercise in pregnancy; 32% of patients that did not exercise prior to pregnancy reported they did not receive counseling. Approximately 32% of patients who exercised and 12% of those who did not exercise pre-pregnancy expressed interest in meeting with a personal trainer for an exercise counseling session. Of women that expressed interest in a personal training session, 20% reported not receiving any exercise counseling. CONCLUSION: Twenty percent of pregnant women were not adequately counseled regarding exercise. Twelve percent of patients who did not exercise prior to pregnancy expressed interest in a personal training session. This illustrates a population of women that is interested in and would benefit from further efforts, encouragement and education regarding physical activity that may not otherwise exercise regularly.